O Bairro Invisível. A Operação da Quinta do Alto no SAAL Lisboa - Rita Magalhães Gorjão Henriques (2021)
This is the story of a neighbourhood. Of the neighbourhood of Quinta do Alto, one of the seven neighbourhoods built under the SAAL program in the city of Lisbon. Starting with the discovery of the estate of the architect Manuel Magalhães, responsible for the operation of Quinta do Alto, between 1975 and 1982, we face the challenge of unveiling and dissecting the process and construction of this complex. This work involves the investigation of a revolutionary and exceptional process in Portugal between 1974 and 1976. It is the constitution of a critical speculation that seeks to contribute to the study of the SAAL operations in Portugal. This essay includes a compilation of drawings, visits, consultation of sources (periodicals of the time, archives, city council files), as well as the study of architectural models and architectural references that served as the basis for the resolution of the housing needs of the population of this area of the city. The Invisible Neighbourhood is an exercise of observation, understanding and analysis of an architectural object that, despite its apparent anonymity, has an author, a peculiar community and story worth telling.